2011
DOI: 10.1111/j.1365-2923.2010.03808.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating candidate reactions to selection practices using organisational justice theory

Abstract: Medical Education 2011: 45: 289–297 Objectives  This study aimed to examine candidate reactions to selection practices in postgraduate medical training using organisational justice theory. Methods  We carried out three independent cross‐sectional studies using samples from three consecutive annual recruitment rounds. Data were gathered from candidates applying for entry into UK general practice (GP) training during 2007, 2008 and 2009. Participants completed an evaluation questionnaire immediately after the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 28 publications
(98 reference statements)
0
50
0
2
Order By: Relevance
“…Further research should explore applicant reactions to the selection process so that perceptions of fairness and justice can be monitored over time. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Further research should explore applicant reactions to the selection process so that perceptions of fairness and justice can be monitored over time. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the use of SJTs for selection into medical school have shown that these beneficial characteristics of SJTs also apply in a medical school context (Koczwara et al 2012;Lievens 2013;Lievens et al 2005;Lievens and Sackett 2012;Patterson et al 2009Patterson et al , 2011Patterson et al , 2015.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The current UK GP selection system is reliable, valid, and generates positive candidate reactions, 14,15,16,17 and uses selection criteria derived from a job analysis study published over 12 years ago in this journal. 9 Although the selection criteria were reviewed using a nationwide survey in 2005, 18 there is a now an urgent need to ensure continued relevance given recent changes in practice.…”
mentioning
confidence: 99%